1995
DOI: 10.3354/meps125205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oyster mariculture on submerged aquatic vegetation:an experimental test in a Pacific Northwest estuary

Abstract: The effects of commercial culture of oysters Crassostrea gigas, on submerged aquatic vegetation (SAV), Zostera manna, were examined w~t h rephcated field expenments in the South Slough estuary Oregon USA Both stake and rack methods of oyster culture resulted In signlf~cant decreases in the abundance of SAV compared to undisturbed reference areas SAV cover in both stake and rack treatments was less than 25% of that In reference plots after 1 yr of culture, and was absent from rack treatments after 17 mo of cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 53 publications
3
35
0
Order By: Relevance
“…The impacts that aquaculture activities may have on seagrass populations are also of increasing concern (Simenstad & Fresh 1995, Neckles et al 2005, Orth et al 2006a) because of the potential negative effects resulting from both recreational and commercial shellfish harvest, including reduced seagrass biomass, density, and percent cover in harvested areas , Everett et al 1995, Boese 2002, Orth et al 2002, Thom et al 2003, Cabaço et al 2005, Neckles et al 2005. Hydraulic dredges used to harvest oysters can cause long-term disruption of eelgrass Zostera marina beds, reducing or even eliminating beds in some cases (Waddell 1964, Phillips 1984.…”
Section: Introductionmentioning
confidence: 99%
“…The impacts that aquaculture activities may have on seagrass populations are also of increasing concern (Simenstad & Fresh 1995, Neckles et al 2005, Orth et al 2006a) because of the potential negative effects resulting from both recreational and commercial shellfish harvest, including reduced seagrass biomass, density, and percent cover in harvested areas , Everett et al 1995, Boese 2002, Orth et al 2002, Thom et al 2003, Cabaço et al 2005, Neckles et al 2005. Hydraulic dredges used to harvest oysters can cause long-term disruption of eelgrass Zostera marina beds, reducing or even eliminating beds in some cases (Waddell 1964, Phillips 1984.…”
Section: Introductionmentioning
confidence: 99%
“…Even though some of the declines may result from natural causes, more than 70% of reported declines are attributed to human-induced disturbances (Short & Wyllie-Echeverria 1996) related to eutrophication or toxic pollutants. Seagrass meadows are also often damaged by mechanical action related to dredging (Onuf 1994), boat activities such as mooring and propeller scars (Zieman 1976, Walker et al 1989, Dawes et al 1997, Creed & Amado Filho 1999, fishing practices (Fonseca et al 1984, De Jonge & De Jong 1992, Everett et al 1995, Boese 2002, Neckles et al 2005, Uhrin et al 2005) and trampling (Eckrich & Holmquist 2000). Mechanical disturbances affect seagrass beds primarily by removing plants, which reduce biomass and has the potential to alter the physical environment.…”
Section: Introductionmentioning
confidence: 99%
“…Certain fishing practices have been shown to reduce seagrass cover (De Jonge & De Jong 1992, Everett et al 1995, Boese 2002, particularly in shallow estuaries and tidal lagoons. Commercial clam harvesting is a traditional and economically important activity in the Ria Formosa tidal lagoon (southern Portugal), representing more than 90% of national clam production (Direcção Regional das Pescas e Aquicultura do Sul pers.…”
Section: Introductionmentioning
confidence: 99%
“…Oysters grown on longlines represented only 4% of the culture area in our study, and again we observed no difference relative to the model-predicted or interpolation-predicted amount of eelgrass cover in these areas at the landscape scale. Effects clearly depend on the structure, with densely planted stakes and oysters grown in bags on racks substantially reducing eelgrass cover in a previous US west coast study (75% and 100% loss, respectively, relative to controls; Everett et al 1995), yet oysters grown on longlines with more open space caused little reduction in eelgrass density and cover (Wisehart et al 2007, Tallis et al 2009). Eelgrass metrics scaled with spacing between longlines due to both shading and dessication of eelgrass that coexisted, but stranded over the top of these lines in Humboldt Bay, California (55−65% cover with 3 m spacing reduced to <15% Researchers elsewhere found reduced eelgrass density, morphometrics, and photosynthesis due to reduced irradiance under suspended bags and oyster baskets, but also showed that the effect was mostly restricted to the area under the aquaculture structures themselves, and severity of effect de pended on the structure design and signature (Bulmer et al 2012, Skinner et al 2013.…”
Section: Oyster Culture Bed Typementioning
confidence: 91%
“…Oysters grown on structures can have additional physical effects, including shading and sediment erosion around the structure. These factors caused 75% reduction in eelgrass cover relative to controls for oyster stake culture and up to 100% loss of eelgrass under oyster racks (Everett et al 1995), yet oysters grown on longlines with more open space caused little reduction in eelgrass density and cover (Wisehart et al 2007, Tallis et al 2009). Further study suggested that eelgrass metrics scaled with spacing between these oyster lines and that both shading and dessication from stranding over the lines contributed to the effect (Rumrill & Poulton 2004).…”
Section: Open Pen Access Ccessmentioning
confidence: 99%